2017
DOI: 10.2147/cia.s140553
|View full text |Cite
|
Sign up to set email alerts
|

BFH-OSTM, a new predictive screening tool for identifying osteoporosis in elderly Han Chinese males

Abstract: PurposeTo develop and validate a new clinical screening tool to identify primary osteoporosis by dual-energy X-ray absorptiometry (DXA) in two elderly Han Chinese male populations.MethodsA cross-sectional study was conducted, enrolling 1,870 community-dwelling and 574 hospital-checkup elderly Han Chinese males aged ≥50 years. All subjects completed a structured questionnaire and had their bone mineral density (BMD) measured using DXA. Using logistic regression analysis in the 1,870 community-dwelling males, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…The serious complications of OP, including osteoporotic fractures, pain and misshapen bones, are associated with a high cost of treatment and prevention, and pose a major socioeconomic burden (17). Abnormal stimulation of osteoclasts generally results in bone loss, which leads to OP, and this disease is primarily characterized by decreased bone mass and disorders of the bone microstructure (18)(19)(20). Current therapies for OP, such as bone resorption inhibitors and bisphosphonate, are mainly focused on the balance of bone remodeling, which is critical during maintenance and regeneration of bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The serious complications of OP, including osteoporotic fractures, pain and misshapen bones, are associated with a high cost of treatment and prevention, and pose a major socioeconomic burden (17). Abnormal stimulation of osteoclasts generally results in bone loss, which leads to OP, and this disease is primarily characterized by decreased bone mass and disorders of the bone microstructure (18)(19)(20). Current therapies for OP, such as bone resorption inhibitors and bisphosphonate, are mainly focused on the balance of bone remodeling, which is critical during maintenance and regeneration of bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In this model [ 15 ], only weight and history of the previous fracture were selected in the ultimate model. The new model had been named the Beijing Friendship Hospital Osteoporosis Self-Assessment Tool for Elderly Male (BFH-OSTM) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have confirmed that it can well identify male osteoporosis, the BFH-OSTM index (cutoff = 70) had a sensitivity of 85% and specificity of 53% for identifying osteoporosis according to the WHO criteria, with an area under the ROC curve of 0.763. However, is difficult to know whether it has any value in detecting and identifying PNOVCF [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Khon Kaen Osteoporosis Study (KKOS) (cutoff < −1) scoring system shared a similar performance with OSTA (cutoff < −1) in Thai women (AUC: 0.64 vs. 0.65) [ 31 ]. The Beijing Friendship Hospital Osteoporosis Self-Assessment Tool (BFH-OST) also performed similarly to OSTA (cutoff = −1) in predicting osteoporosis in Chinese Han women and men (AUC: 0.795–0.797 vs. 0.732–0.782), despite having a higher sensitivity (73.58–89.92% vs. 50.42–65.28%) [ 32 , 33 ]. Among the South Indian elderly, the performance of the Male Osteoporosis Risk Estimation Score (MORES) (cutoff = 6) was also equivalent to OSTA (cutoff ≤ 2) (AUC: 0.760 vs. 0.778) [ 34 ].…”
Section: Performance Of Ost Among Asiansmentioning
confidence: 99%